The impact of harmonising Australia's workplace health and safety laws on workers compensation - Anam Bilgrami; Henry Cutler; Kompal Sinha (Global Labor Organization (GLO), 2021)
We analyse the impact of harmonising workplace health and safety laws in Australia on workplace injury and disease by estimating effects on the probability of receiving workers compensation in the past year. The introduction of the reform in all but two Australian states created a unique, region-based natural experiment. We exploit this regional variation to perform difference-in-difference estimation on a panel data sample of workers from the Household, Income and Labour Dynamics in Australia survey, accounting for a diverse range of individuallevel covariates associated with workers compensation claiming. We find harmonisation reduced the probability of receiving workers compensation in treated states by 0.9 percentage points (p=0.047). This is likely to have resulted from increased enforcement activity by state governments and increased managerial focus on improving workplace health and safety. Subgroup analysis suggests the high-risk construction industry had a larger and more significant reduction of 2.9-3.6 percentage points (p=0.030). We suggest the construction industry had a greater potential for achieving reductions in workplace injury and disease due to a higher level of underlying workplace risk and the introduction of construction specific legislative requirements imposed by harmonisation.
Keywords: D04; I18; J28; J38; L52; 330; workplace health and safety; Australia; workers compensation; causal analysis; workplace injury